IMIA Presidential Retrospectives on Medical Informatics - Ball, M.J.; van Bemmel, J.H.; Kaihara, S. (Yearbook of Medical Informatics, 2007)
The International Medical Informatics Association (IMIA) celebrates its 40th anniversary in 2007. Three IMIA Presidents from three continents were invited to give their personal retrospectives on the world’s largest organization in medical informatics.Reports, based on personal reminiscenses.IMIA was established in the 1970s by individuals already active in medical informatics in their home countries. It has evolved into a strong international organization based on the mutual trust and friendship of members throughout the world. IMIA serves as a ‘bridge’ organization both within an inter organizational context and within the broader context of IMIA’s professional aims. Being a driving motor for successive waves of change in the field, IMIA helps to significantly improve health care by building bridges across regions, disciplines, and professions, to bridge the distances around the globe.Geissbuhler A, Haux R, Kulikowski C, editors. IMIA Yearbook of Medical Informatics 2007.
Keywords: Medical informatics; health informatics; nursing informatics; biomedical informatics; International Medical Informatics Association; IMIA